Accelerometer profile recognition of swimming strokes - Slawson, S. E.; Justham, L. M.; West, A. A.; Conway, P. P.; Caine, M. P.; Harrison, R. (The Engineering of sport 7, Volume 1, 2008)
The use of technology in sports performance analysis is a rapidly increasing practise. Tools for analysis aim to provide useful information to Supplement coach knowledge and improve feedback in the development of athletes. In swimming the use of subjective video analysis is wide-spread, however, unlike some other Sports, there are few quantitative measures of performance. Quantitative measures, such as intra cyclic variations of stroke characteristics, have the potential to provide more specific performance metrics from which to make improvements. Such measures are currently not widely available to coaches, support staff and swimmers, due to the infancy or lack of sufficiently developed technologies. The research outlined in this paper has explored the relationship between stroke characteristics and how they are represented by accelerometer data. Each of the four competition swimming strokes has been investigated, where swimmers instrumented with a portable sensor were asked to perform their normal swimming strokes. During each swimming trial, sensor and video data were recorded. Preliminary testing has shown that accelerometer data can be useful in the determination of simple stroke characteristics, for example stroke rate and duration, and that differences in profiles can be attributed to a certain stroke or swimmer. Future work is required to broaden this understanding and support the outcomes already generated from this preliminary study.